Magic Realism In Central Java Folklore - Amara Arsyisyah Faradita; Budi Tri Santosa (Universitas Muhammadiyah Semarang, 2022)
The influence of literary schools in the magical realism can be seen in Indonesian literary works. This paper describes the characteristics of magical realism theory in Indonesian folklore. The problem discussed is the erosion of culture, especially in Indonesia, based on elements that characterize magical realism and the context of folklore in terms of the narrative strategy. In this study, data was obtained through data collection methods using elements from concepts that were compiled based on magical realism theory to answer the problems. The concept used in explaining the problem is categorization of data. Based on this, the research was carried out through the stages of data collection, descriptive and interpretive data analysis, and making conclusions. In the discussion, it is found out the characteristics of magical realism theory in Indonesian folklore. Through these characteristics and the relationships between elements, the issue of myths in Indonesia is underlined.